Acetazolamide-Induced Aseptic Meningitis in a Female Adolescent with Idiopathic Intracranial Hypertension: A Case Report - Gupta, Rekha; Barton, Chris; Puri, Vinay (Journal of Pediatric Neurology, 2020)
Drug-induced aseptic meningitis (DIAM) has been documented for many years and is considered a diagnostic and patient management challenge. Associated medications include nonsteroidal anti-inflammatory drugs, antibiotics, and monoclonal antibodies, but no cases associated with acetazolamide have been reported. We briefly review a case of a 15-year-old female patient with history of idiopathic intracranial hypertension whose symptoms of aseptic meningitis associated with the use and increase of acetazolamide. DIAM should be considered a possibility in any patient with meningeal symptoms, pleocytosis, and negative cerebrospinal fluid culture. This is the first known case linking acetazolamide to DIAM.
Keywords: headache; idiopathic intracranial hypertension; acetazolamide; drug-induced aseptic meningitis